Complete asymmetric polarization conversion at zero-eigenvalue exceptional points of non-Hermitian metasurfaces - Oh Donghak; Baek Soojeong; Lee Sangha; Lee Kyungmin; Park Jagang; Liu Zhaowei; Kim Teun-Teun; Min Bumki (Nanophotonics)
Non-Hermitian systems can be tuned to exhibit exceptional points, where both eigenvalues and eigenstates coalesce concurrently. The inherent adaptability of photonic non-Hermitian systems in configuring gain and loss has allowed us to observe a plethora of counterintuitive phenomena, largely as a consequence of the eigenspace reduction at these exceptional points. In this work, we propose a non-Hermitian metasurface that, through the incorporation of gain, enables complete asymmetric polarization conversion at an exceptional point with a zero eigenvalue. Specifically, we provide numerical evidence for this concept by designing a non-Hermitian metasurface that facilitates polarization conversion from right to left circular polarization, while preventing conversion in the reverse direction and co-polarized transmission. Furthermore, our investigation reveals that this specific form of complete asymmetric polarization conversion results in maximum circular dichroism in transmission, thereby eliminating the need for external chirality or three-dimensional helical structures. This non-Hermitian technique offers an intriguing approach to designing polarization-sensitive optical devices and systems, further expanding their functionalities and capabilities.